2018
DOI: 10.1016/j.jid.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Endothelial to Mesenchymal Transition Increased Fibrosis via Deleting Notch Signaling in Wound Vasculature

Abstract: Skin wound healing in adults is characterized by a peak of angiogenesis followed by regression of the excessive vasculature in parallel with collagen deposition and fibrosis in the wound. We hypothesized that regressing vessels in healing wounds were in fact entering an endothelial to mesenchymal transition contributing to scarring. Using vascular-specific fate tracking (Cdh5-cre/ROSA-YFP mice), full-thickness excisional wounds were analyzed to reveal a time-dependent transition from endothelial phenotype char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Interestingly, this effect is specific for diabetes, where Notch1 is overactivated, and inhibition of Notch signaling using GSIs or skin-specific Notch1 gene ablation did not affect wound healing in nondiabetic control animals. The latter observation receives support from other studies, reporting that in nondiabetic animals, there was either no effect (43) or even delaying (22,44) of the wound-healing rate when Notch signaling was blocked.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, this effect is specific for diabetes, where Notch1 is overactivated, and inhibition of Notch signaling using GSIs or skin-specific Notch1 gene ablation did not affect wound healing in nondiabetic control animals. The latter observation receives support from other studies, reporting that in nondiabetic animals, there was either no effect (43) or even delaying (22,44) of the wound-healing rate when Notch signaling was blocked.…”
Section: Discussionsupporting
confidence: 67%
“…What we observed was a trend toward reduced angiogenesis in our mice at D14 wounds; however, this difference was not statistically significant. Further studies investigating long-term effects on endothelial-to-mesenchymal transition (EndMT) could also be useful in studying long-term scar formation due to the reduction in NLRP3-associated inflammation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β and Notch signaling cooperate to induce the expression of Snail, thereby downregulating the expression of VE-cadherin and promoting EndMT (Fu et al, 2009). In contrast, Patel et al (2018) demonstrated that EC specific deletion of Notch signaling resulted in enhancement of EndMT since more CD31 − FSP + cells were detectable in skin wounds of endothelial specific transcription factor Rbpj-deficient mice. Interestingly, TGF-β1 expression was found to be increased in these CD34 − /FSP-1 + wound ECs, which suggests that TGF-β is the main driver of EndMT in mice deficient for endothelial specific Notch signaling (Patel et al, 2018).…”
Section: Interplay With Other Signaling Pathways That Mediate or Regumentioning
confidence: 97%